Eco-Efficiency and Stock Market Volatility: Emerging Markets Analysis - Alicia Fernanda Galindo-Manrique (Administrative Sciences, 2021)
Climate change, the accelerated industrialization of emerging countries, as well as the growing demand for transparency from stakeholders, are all factors that influence the environmental performance of companies. Thus, eco-efficient behavior can improve financial performance by increasing wealth generation and decreasing the volatility of listed financial assets. There is a lot of previous literature showing diverse results of the effect of eco-efficiency on corporate profitability, but this is not the case when we refer to risk. This study analyzes the relationship between eco-efficient behavior and the share price volatility of companies traded in emerging markets. For this purpose, a sample of 346 companies listed in 24 countries was studied for the period between 2010 and 2017. The results show a positive effect. Thus, the recommendation is that a clear commitment to eco-efficient investment can improve the environmental impact of companies, from the private, public, and institutional spheres.